The ethics of invention : technology and the human future - Jasanoff, Sheila author. (New York : W.W. Norton e Company, 2016)
The power of technology? -- Risk and responsibility? -- The ethical anatomy of disasters? -- Remaking nature? -- Tinkering with humans? -- Information's wild frontiers? -- Whose knowledge, whose property? -- Reclaiming the future? -- The ethics of invention?